Abnormalities of Inter- and Intra-Hemispheric Functional Connectivity in Autism Spectrum Disorders: A Study Using the Autism Brain Imaging Data Exchange Database - Lee, Jung Min; Kyeong, Sunghyun; Kim, Eunjoo; Cheon, Keun-Ah (Frontiers in Neuroscience, 2016)
Recently, the Autism Brain Imaging Data Exchange (ABIDE) project revealed decreased functional connectivity in individuals with Autism Spectrum Disorders (ASD) relative to the typically developing controls (TDCs). However, it is still questionable whether the source of functional underconnectivity in subjects with ASD is equally contributed by the ipsilateral and contralateral parts of the brain. In this study, we decomposed the inter- and intrahemispheric regions and compared the functional connectivity density (FCD) between 458 subjects with ASD and 517 TDCs from the ABIDE database. We quantified the inter- and intrahemispheric FCDs in the brain by counting the number of functional connectivity with all voxels in the opposite and same hemispheric brain regions, respectively. Relative to TDCs, both inter- and intrahemispheric FCDs in the posterior cingulate cortex, lingual/parahippocampal gyrus, and postcentral gyrus were significantly decreased in subjects with ASD. Moreover, in the ASD group, the restricted and repetitive behavior subscore of the Autism Diagnostic Observation Schedule (ADOS-RRB) score showed significant negative correlations with the average interhemispheric FCD and contralateral FCD in the lingual/parahippocampal gyrus cluster. Also, the ADOS-RRB score showed significant negative correlations with the average contralateral FCD in the default mode network regions such as the posterior cingulate cortex and precuneus. Taken together, our findings imply that a deficit of non-social functioning processing in ASD such as restricted and repetitive behaviors and sensory hypersensitivity could be determined via both inter- and intrahemispheric functional disconnections.